PEMBIAYAAN MIKRO UMKM DESA WISATA; KAJIAN EKONOMI KELEMBAGAAN - M. Yuwana Marjuka (Journal of Tourism Destination and Attraction, 2022)
Coordination and synchronization are the most urgent and difficult aspects of inter and intra government intervention through program for Micro, Small and Medium Enterprise (UMKM) in Indonesia. First, this article is conducted to find out solution for the problem relating to the empowerment of that many laws and government orders that are not synchronous, harmonious, overlapping to each other’s and they prone to cause of inequality distribution program relate to micro finance for SME. Second, this paper is a critical review of a research and mapping for SME conducted by Tim Kebijakan Peningkatan Kapasitas ekonomi sekretariat TNP2K and Lembaga Demografi Fakultas ekonomi dan bisnis Univesitas Indonesia (TNP2K, 2020). The title of these research is: “(Pemetaan Program Pemberdayaan Usaha Mikro, Kecil, Dan Menengah (UMKM). Their research is important because it is a pioneer research mapping of government interventions and numerous programs linking empowerment and financing attainment by Small and Medium Enterprise. The research found many and various UMKM (64) program designed and conducted by more than 22 ministries and government organizations (K/L) at the year of 2019. But the research found that there are so many inefficiencies and overlap over the programs cause of lack of coordination and synchronization among the ministries and government organization. On the other side, the research also has limitations, especially in the “academic and economics theory frame work”. These articles try to criticize and interpretive of the such phenomenon by and based on “agency theory” approach. Consequently, the academic and economics theory should be derived from and reverse to the New Institutional Economics (NIE). According to NIE there are some relevant theories such as Agent-Principal theory, Transaction cost theory, property rights and contract theory need to be implemented in these government institutional research.